Factors Predictive of the Level Of Physical Activity (PA) in Patients with Gonarthrosis in Sub-Saharan Africa - Tiaho, Yirozounlomian; Ayouba, Tinni Ismael; Sougue, Charles; Tougma, Gouzé-Wend Louis; Kabore, Fulgence; Gandema, Salifou; Zabsonre/Tiendrebeogo, Wendlassida Joelle Stéphanie; Ouedraogo, Dieu-Donné (Surabaya Physical Medicine and Rehabilitation Journal, 2024)
Background: Our aim was to determine the predictive factors of the level of physical activity (PA) in patients with gonarthrosis in the city of Ouagadougou (Burkina Faso). Methods: This was a cross-sectional, descriptive and analytical study based on clinical records, conducted from January 9 to 27, 2023. Using the International Physical Activity Questionnaire (IPAQ), we assessed the level of PA in patients followed at CHU-Bogodogo for gonarthrosis. The significance threshold p<0.05 was retained. Results: Sixty-seven patients were included. Fifty-six were women (83.58%). The mean age was 59.87± 12.53 years. Hypertension was noted in 34 patients (50.75%), diabetes in 16 (23.88%). The mean BMI was 28.70kg/m2± 6.73. Gonarthrosis was bilateral in 49 patients (73.13%). Gonarthrosis patients had a moderate level of PA, with a mean IPAQ score equal to 635.24±135 MET-minutes/week. 45 patients (67.16%) had a low level of physical activity (Ë‚ 600 MET-minutes/week). In bivariate analysis, low PA was associated with age over 65 [OR=5.62, (CI=1.45-21.73), p<0.001], hypertension [OR=2.83, (CI=1.27-6.31), p<0.001], diabetes [OR=2.14, (CI=1.13-5.89), p<0.031], and overweight [OR=2.43, (CI=1.17-6.12), p<0.026]. Moderate PA was associated with age under 65 [OR=1.71, (CI=1.25-2.34), p<0.005] and absence of hypertension [OR=1.86, (CI=1.19-2.89), p<0.012]. Conclusion : Gonarthrosis patients have a moderate level of PA. Factors associated with low PA were advanced age and sedentary comorbidities. Key words: Gonarthrosis, physical activity, Ouagadougou/Burkina Faso